Top 10 grossest animals - Maloney, Brenna (New York : Scholastic Inc., 2025)
"There are so many gross animals! Some of them smell bad. Some of them are slimy. Some like to eat icky things. Some are snotty, squishy, or even rotten! Learn all about the gross amphibians, birds, insects, mammals, and reptiles in our wild world. Count down from 10 to 1 and discover which one is the absolute grossest!"--
Ages 5-7
Grades K-1